Phyphox-Integrated Problem-Based E-Worksheets to Train Students’ Collaborative Skills in Physics Learning - Alfin Auliya; Sri Latifah; Sodikin Sodikin; M. Sayyidul Abrori (CV FOUNDAE, 2025)
National educational progress relies heavily on innovative teaching methods, particularly in physics learning. This study focuses on the development and feasibility assessment of an interactive electronic student e-worksheet based on a Problem-Based Learning (PBL) approach and integrated with the Phyphox application as a virtual laboratory tool to support students' collaborative skills in physics le arning. Employing the 4D development model (Define, Design, Develop, Disseminate), the research was conducted up to the Develop stage, emphasizing product feasibility testing. Validation was carried out by subject matter and media experts, while practicality testing involved two teachers and 42 students from a public senior high school in Bandar Lampung. Data collection methods included interviews, observations, and Likert-scale questionnaires. The e-worksheet achieved high feasibility scores, 88.7% for media quality and 93.3% for content. Practicality assessments from teachers and students ranged from 93.0% to 95.2%, indicating excellent usability. The findings demonstrate that integrating Phyphox into the e-worksheet is both highly feasible and perceived as practical; however, future studies should examine its effectiveness in enhancing collaboration and learning outcomes. This research contributes to advancing technology-based interactive learning media with the potential to improve educational quality. Further investigations are recommended to evaluate the effectiveness of this tool across different academic levels and physics topics.